SUPPLY CHAIN MANAGEMENT IN TRANSLATION INDUSTRY - Mujazin, Mujazin; Nababan, M.R.; Santosa, Riyadi; Hari Wibowo, Agus (International Journal of Supply Chain Management, 2020)
Abstract- Islamic religious texts are sensitive texts, when translated they must continue to show their religiosity. Supply chain strategy in translation industry can improve its quality and honesty in the predefined process. This study uses a qualitative method, which revealed the character of supply chain in translation. After conducting research it was found that the religiosity of the text could be judged based on 1. The mention of the name of ALLAH than Tuhan, 2. The family of languages used, 3. The techniques used and 4. The frequency of Islamic religious terms that emerged. Translators have required two things as mentioned in some previous studies, namely good knowledge related to grammar and culture. Besides these two important things also must be owned by the translator is honesty and well-delivered.